Privatization strategy in university education in light of the Kingdom of Saudi Arabia’s Vision 2030 - Alghamdi, Abeer Saeed (Edelweiss Applied Science and Technology, 2025)
The practical research aims to study the strategy of privacy in university education in light of the vision of the modern Kingdom of Saudi Arabia 2030, relying on descriptive rules and referring to a group of references and sources and the vision of the Kingdom of Saudi Arabia with the aim of defining privacy, its dimensions, and trends towards privacy in university education, in addition to its positive applications in university education and the challenges facing its applications and the harmful effects of it. The current research has reached a set of the most important results, the most prominent of which is that applying the specialized strategy in the field of university education leads to diversity in specializations, in addition to the presence of educational trends and keeping pace with the development of technology in the field of teaching. The study group presented recommendations that aim to address the role of privacy in university education by working to provide an appropriate infrastructure for an effective environment and expanding the establishment of student institutions for the labor market according to the requirements of work and the presence of university life that supports continuous learning processes within the framework of sustainability.